EQUIP training the trainers: an evaluation of a training programme for service users and carers involved in training mental health professionals in user‐involved care planning. Issue 6 (20th January 2017) - Fraser, C.; Grundy, A.; Meade, O.; Callaghan, P.; Lovell, K.
Accessible summary: What is known on the subject?: UK NHS policy highlights the importance of user and carer involvement in health professional training. We know little about service user and carer motivations and experiences of accessing training courses for delivering training to health professionals and how well such courses prepare them for delivering training to healthcare professionals. 'Involvement' in training has often been tokenistic and too narrowly focused on preregistration courses. There is limited data on how best to prepare and support potential service user and carer trainers. What does this paper add to existing knowledge?: This study adds to the international literature by highlighting service user and carer motivations for accessing a training course for delivering training to health professionals. Service users and carers wanted to gain new skills and confidence in presentation/facilitation as well as to make a difference to healthcare practice. We also learned that service users desired different levels of involvement in training facilitation – some wanted to take a more active role than others. A one‐size‐fits‐all approach is not always appropriate. Encountering resistance from staff in training was a previously unidentified challenge to service user and carers' experience of delivering training in practice and is a key challenge for trainers to address in future. Professional training involvement can be enhanced via specialist training such as the EQUIP training the trainers programme evaluated here. What are the implications for practice?: When training service users and carers to deliver training to mental health professionals, it is important that service users are equipped to deal with resistance from staff. It is important that service user and carer roles are negotiated and agreed prior to delivering training to healthcare professionals to accommodate individual preferences and allay anxieties. Training for service users and carers must be offered alongside ongoing support and supervision. Mental health nurses (and other health professionals) will be better able to involve service users and carers in care planning. Service users and carers may feel more involved in care planning in future. Abstract: Introduction: Limited evidence exists on service user and carer perceptions of undertaking a training course for delivering care planning training to qualified mental health professionals. We know little about trainee motivations for engaging with such train the trainers courses, experiences of attending courses and trainees' subsequent experiences of codelivering training to health professionals, hence the current study. Aim: To obtain participants' views on the suitability and acceptability of a training programme that aimed to prepare service users and carers to codeliver training to health professionals. Method: Semi‐structured interviews with nine service users and carers attending the training programme. Transcripts were analysed using inductive thematic analysis. Results: Participants' reasons for attending training included skill development and making a difference to mental health practice. Course content was generally rated highly but may benefit from review and/or extension to allow the range of topics and resulting professional training programme to be covered in more depth. Trainees who delivered the care planning training reported a mix of expectations, support experiences, preparedness and personal impacts. Implications for Practice: Mental health nurses are increasingly coproducing and delivering training with service users and carers. This study identifies possibilities and pitfalls in this endeavour, highlighting areas where user and carer involvement and support structures might be improved in order to fully realize the potential for involvement in training.